2014
DOI: 10.4314/bcse.v28i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among fluoride and metals in irrigation water and soils of Ethiopian Rift Valley

Abstract: ABSTRACT. The levels of fluoride and selected metals in Ethiopian Rift Valley soils and irrigation water in the nearby sources were determined by fluoride ion selective electrode and flame atomic absorption spectrophotometer, respectively. The pH, conductivity, salinity and total dissolved solids in water and soil samples were also determined. Accuracy of the optimized procedure was evaluated using standard addition (spiking) method and an acceptable percentage recovery was obtained. The fluoride concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The rift floor is fully covered by lacustrine sediments and acidic rocks (welded and unwelded tuff, ash flow tuff, pumice and obsidian rich lava) (Chernet, 1982;Legesse et al, 2003). It has also a high concentration of F À (Gizaw et al, 2014), which is of great health concern around the study area and in most parts of the rift system. This accounts for the richness of the drainage waters in dissolved silicon, Na + and K + .…”
Section: Area Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rift floor is fully covered by lacustrine sediments and acidic rocks (welded and unwelded tuff, ash flow tuff, pumice and obsidian rich lava) (Chernet, 1982;Legesse et al, 2003). It has also a high concentration of F À (Gizaw et al, 2014), which is of great health concern around the study area and in most parts of the rift system. This accounts for the richness of the drainage waters in dissolved silicon, Na + and K + .…”
Section: Area Descriptionmentioning
confidence: 99%
“…This accounts for the richness of the drainage waters in dissolved silicon, Na + and K + . It has also a high concentration of F À (Gizaw et al, 2014), which is of great health concern around the study area and in most parts of the rift system. In contrast, Ca 2+ and Mg 2+ are relatively depleted.…”
Section: Area Descriptionmentioning
confidence: 99%
“…Some studies have been reported on the mineral composition of lake water, river water, and irrigation waters in Ethiopia [11,34,35]. Physicochemical analysis of drinking water has also been studied to assess the quality of drinking water in different cities and regions of Ethiopia [7,33,36,37].…”
Section: Introductionmentioning
confidence: 99%